2018
DOI: 10.1093/mnras/sty2255
|View full text |Cite
|
Sign up to set email alerts
|

Early formation of carbon monoxide in the Centaurus A supernova SN 2016adj

Abstract: We present near-infrared spectroscopy of the NGC 5128 supernova SN 2016adj in the first 2 months following discovery. We report the detection of first overtone carbon monoxide emission at ∼ 58.2 d after discovery, one of the earliest detections of CO in an erupting supernova. We model the CO emission to derive the CO mass, temperature and velocity, assuming both pure 12 CO and a composition that includes 13 CO; the case for the latter is the isotopic analyses of meteoritic grains, which suggest that core colla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…From −5 to +82 d, He I λ10830 absorption features correspond to v ph values from ∼20 000-17 000 km s −1 , respectively. The He I λ10830 velocity is higher for SN 2012au in comparison with that observed for SN 2016adj (∼14000 km s −1 ) by Banerjee et al (2018). However, we caution here that a small contribution from Pγ , C I λ10686, Mg II λ10926, and Si I λ10991 to the He I λ10830 feature could also be present, as also discussed by Milisavljevic et al (2013); see also Medhi et al (1996) and Wheeler et al (1998).…”
Section: Nir Spectroscopic Evolutionsupporting
confidence: 59%
See 1 more Smart Citation
“…From −5 to +82 d, He I λ10830 absorption features correspond to v ph values from ∼20 000-17 000 km s −1 , respectively. The He I λ10830 velocity is higher for SN 2012au in comparison with that observed for SN 2016adj (∼14000 km s −1 ) by Banerjee et al (2018). However, we caution here that a small contribution from Pγ , C I λ10686, Mg II λ10926, and Si I λ10991 to the He I λ10830 feature could also be present, as also discussed by Milisavljevic et al (2013); see also Medhi et al (1996) and Wheeler et al (1998).…”
Section: Nir Spectroscopic Evolutionsupporting
confidence: 59%
“…The spectra presented are in rest-frame wavelengths and also corrected for extinction using E(B − V) = 0.063 mag (Milisavljevic et al 2013), exhibiting a decrease in flux with wavelength, typically observed in SESNe. Line identifications of NIR spectra were done following Gerardy et al (2002), Hunter et al (2009), Banerjee et al (2018), andRho et al (2021). The vertical red bands denote regions of poor atmospheric transparency.…”
Section: Nir Spectroscopic Evolutionmentioning
confidence: 99%
“…The detection of CO in SN 2020oi, only ∼63 days since the explosion (∼54 and 52 days after B-and V-band maximum, respectively), is one of the earliest CO detections in an SN of any type. There are only two other SNe where a similar, early CO detection was made, namely, SN 2013ge (Drout et al 2016) and SN 2016adj (Banerjee et al 2018). Detections of CO were reported in SN Ic SN 2000ew and SN 2007gr at day 90 and 70 (post-B maximum), respectively (Gerardy et al 2002;Hunter et al 2009).…”
Section: Co and Dust Formation In Type Ic Sn 2020oimentioning
confidence: 75%
“…We have estimated the CO mass in SN 2020oi using the LTE model developed by Das et al (2009), which assumes optically thin emission and a pure 12 C 16 O composition. Earlier applications of the model include SN 2017eaw (Rho et al 2018a), SN 2016adj (Banerjee et al 2018), and several novae (Banerjee et al 2016;Joshi et al 2017). We adopted a straight continuum (for the dust emission) passing through the two minima (2.01-2.08 μm and 2.155-2.17 μm) in the spectrum between 2.00 and 2.23 μm.…”
Section: Co and Dust Formation In Type Ic Sn 2020oimentioning
confidence: 99%
See 1 more Smart Citation